Some More Findings on Tantalum Tungstate: A Crystalline Ion Exchange Material - Gupta, A.P.; Thakur, J.S. (Asian Journal of Chemistry, 2010)
A new crystalline phase of tantalum tungstate through hydrofluoric acid medium abbreviated as TaW(HF) in this article has been synthesized. Its i.e.c. composition and other analyses i.e. TGA, DSC, Electrophotographs i.r. and X-ray have been reported. The d values, Miller indices (h, k, l) and unit cell constant (a) have been calculated. The analysis of these data shows that the phase belongs to FCC (face centered cubic) system.